Dry Lab – Laboratorium Virtual Untuk Anlisa Rekayasa Lumpur Pemboran - M. Mahlil Nasution; Edy Soesanto (JURNAL BHARA PETRO ENERGI, 2022)
Abstract Dry Lab is a virtual laboratory design. We called also as a laboratory of the future. Dry Lab was designed because of the increasingly advanced computerized especially Artificial Intelligence for making a simulator that can function to simulate a tool wich is can similiar with the real condition so that it gets the same results as when run in a conventional laboratory. With the existence of this Simulator technology, then I try to make a virtual simulator for drilling mud analysis which is very much needed in the world of oil engineering education especially and also needed in the world of oil and gas industry, especially when conducting drilling activities. Keywords: Dry Lab, Artificial Intelligence, virtual simulator, drilling mud. Abstrak Dry Lab adalah suatu rancangan virtual laboratorium. Dapat juga dikatakan sebagai Laboratorium masa depan. Dry Lab dirancang karena semakin majunya ilmu komputerisasi Artificial intelligence dalam membuat suatu simulator yang dapat berfungsi mensimulasikan suatu alat sesuai dengan cara kerja aslinya sehingga mendapatkan hasil yang sama seperti saat dijalankan di Laboratorium konvensional.Dengan adanya teknologi Simulator ini, maka saya mencoba membuat suatu simulator virtual untuk analisa lumpur pemboran yang sangat dibutuhkan dalam dunia pendidikan Teknik perminyakan khususnya dan juga dibutuhkan di dalam dunia industri Migas terutama saat melakukan kegiatan pemboran. Kata kunci: Dry Lab, Artificial intelligence, simulator virtual, lumpur pemboran. Reference: Agusman, A. R., Rasyid, A., & Lesmana, D. L. (2022). Evaluasi Water Shut Off Dan Membuka Lapisan Baru Sumur Bagong Di Lapangan Lesma. JURNAL BHARA PETRO ENERGI, 38-43. Aly Rasyid, A. R. (2021). Seleksi Material Untuk Casing Sumur Migas & Geothermal–Buku Referensi. Composition and Properties of Drilling and Completion Fluids: Seventh Edition, Caenn, RyenDarley, H. C.H. and Gray, George R. (2016) Composion And Properties Of Drilling And Complition Fluids,  H.C.H Darley and George R. Gray J.T. Patton (New Mexico State U.) P.F. Phelan (Los Alamos Natl Laboratory), Well Damage Hazards Associated With Conventional Completion Fluids Khodja, M., Khodja-Saber, M., Canselier, J. P., Cohaut, N. and Bergaya, F. (2010) ‘Drilling fluid technology: performances and environmental considerations’, Product and Services, From R&D to final solutions, pp. 227-232. Available at: http://cdn.intechopen.com/pdfs-wm/12330.pdf Nasution, M. M., Rasyid, A., & Pahrudin, G. (2022). Desain Formulasi Lumpur Untuk Pemboran Panas Bumi Di Sumur GG-01. JURNAL BHARA PETRO ENERGI, 11-18. Rasyid, A., Mardiana, R. Y., Budiono, K., & Noviasta, B. (2021, December). Drilling optimization in geothermal exploration wells using enhanced design of conical diamond element bit. In Asia Pacific Unconventional Resources Technology Conference, Virtual, 16–18 November 2021 (pp. 1795-1808). Unconventional Resources Technology Conference (URTeC). Rasyid, A., Soesanto, E., & Nababan, E. N. (2022). Evaluasi dan Optimasi Desain Casing Sumur Pemboran dengan Metode Maximum Load di Sumur ENN-1 di Lapangan Batuwangi. JURNAL BHARA PETRO ENERGI, 1-10. Rasyid, A. (2019). Pemanfaatan Wellbore Strengthening Agent Selama Pengeboran di Onshore Sumatera Bagian Utara Indonesia. Jurnal Jaring SainTek, 1(2). Rudi Rubiandini R.S, Buku Teknik Pemboran Volume 1, Bandung, 2015 Virtual and Physical Experimentation in Inquiry-Based Science Labs: Attitudes, Performance  and Access.Journal of Science Education and TechnologyPyatt, Kevin.,Sims, Rod, 2012 Virtual laboratories in engineering education: the simulation lab and remote labComputer Applications in Engineering Education.Balamuralithara, B. Woods, P. C. 2009 Agusman, A. R., Rasyid, A., & Lesmana, D. L. (2022). Evaluasi Water Shut Off Dan Membuka Lapisan Baru Sumur Bagong Di Lapangan Lesma. JURNAL BHARA PETRO ENERGI, 38-43.